Biotechnology, agriculture and development - Phillips, Peter W. B. (Edward Elgar Pub. Ltd, 2015)
Recent innovations in agriculture and food technologies have brought benefits to many countries, particularly in developing regions, but information about the extent of these has often been sparse. This research review examines the best papers on the subject to form a comprehensive, global perspective on the impacts of agricultural biotechnology around the world. With an emphasis on the economic, environmental, health and food security aspects of agbiotech, Biotechnology, Agriculture and Development will prove to be an invaluable resource for academics, students and researchers alike
Keywords: Economic development; Agricultural biotechnology; Food / Biotechnology; Agricultural innovations; Food industry and trade / Technological innovations; Genetically modified foods; Agriculture / Economic aspects; Electronic books